2014
DOI: 10.1177/0192513x14547417
|View full text |Cite
|
Sign up to set email alerts
|

“When We Do Sit Down Together”

Abstract: Regular family meal times have been associated with enhanced family cohesion and positive developmental outcomes for children–youth, especially in White and/or middle-class families. Less is known about the meal time experiences of low-income African American families. Guided by a family resilience perspective, this study examines meal times among a sample of low-income African American caregivers of preschoolers in an inner-city neighborhood. We conducted in-depth qualitative interviews and a photo elicitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 62 publications
(100 reference statements)
0
10
0
Order By: Relevance
“…Larson and colleagues explain that mealtime is seen as a vehicle of culture because ‘through mealtime activities and conversation, family members often enact and reaffirm cultural meanings and create new meaning’ (Larson, Branscomb & Wiley 2006:3). Jarret, Bahar and Kersh (2014) showed that low-income African American caregivers showed that they valued family mealtimes and acknowledged the benefits for family life. Various studies have shown the benefits of family mealtimes; this activity provides an opportunity for children to learn new words in context (Beals 1997), for parents to listen to children talk about their daily lives (Fulkerson et al 2010) and has also been associated with enhancing family cohesion and contributing to positive developmental outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Larson and colleagues explain that mealtime is seen as a vehicle of culture because ‘through mealtime activities and conversation, family members often enact and reaffirm cultural meanings and create new meaning’ (Larson, Branscomb & Wiley 2006:3). Jarret, Bahar and Kersh (2014) showed that low-income African American caregivers showed that they valued family mealtimes and acknowledged the benefits for family life. Various studies have shown the benefits of family mealtimes; this activity provides an opportunity for children to learn new words in context (Beals 1997), for parents to listen to children talk about their daily lives (Fulkerson et al 2010) and has also been associated with enhancing family cohesion and contributing to positive developmental outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Many households face barriers in the daily orchestration of family meals, such as scheduling conflicts and lack of time, limited resources, scarcity of help, tiredness, lack of skills or confidence [8,30,[77][78][79][80][81] (Table 4). The existence of these barriers is what differentiates everyday domestic commensality from exceptional commensality.…”
Section: Challenges Of Family Meals 481 Barriers To Having Regular Family Dinnersmentioning
confidence: 99%
“…It is important to note that while much research has recognized the benefits of mealtimes among families of racially/ethnically and socioeconomically diverse communities (Robson et al, 2020; Smith et al, 2022), few studies have examined disparities of or barriers to mealtimes by racial/ethnic groups. For example, within Black families, researchers have found that caregivers valued family mealtimes and acknowledged the benefits; however, several barriers did not allow them to have regular family mealtimes (Jarrett et al, 2016). Given that structural inequalities may disproportionately create barriers to family meals among different racial/ethnic groups (Skala et al, 2012), more research must be done to understand family mealtimes across race/ethnicity.…”
Section: Benefits Of Mealtimesmentioning
confidence: 99%
“…There has been some support in previous literature suggesting that adversities associated with racial and structural inequalities in the United States have contributed to infrequent mealtimes. In a qualitative study of low-income Black mothers of preschoolers, researchers found work that provided low wages, was physically demanding, and could not provide consistent schedules all led to infrequent family meals and overreliance on fast food (Jarrett et al, 2016). Although studies have found that non-Hispanic Black families are still less likely to eat meals together when important correlates of adversities (namely income and socioeconomic status) are controlled (Flores et al, 2005), no study to date has examined specific adversities or how these traumatic events influence differences in mealtime frequencies among different ethnic and racial groups.…”
Section: Adverse Childhood Experiences and Family Mealtimesmentioning
confidence: 99%
See 1 more Smart Citation